The views of migrant health workers living in Austria and Belgium on return migration to sub-Saharan Africa. Issue 1 (June 2016) - Poppe, Annelien; Wojczewski, Silvia; Taylor, Katherine; Kutalek, Ruth; Peersman, Wim
Abstract Background The negative consequences of the brain drain of sub-Saharan African health workers for source countries are well documented and include understaffed facilities, decreased standards of care and higher workloads. However, studies suggest that, if migrated health workers eventually return to their home countries, this may lead to beneficial effects following the transfer of their acquired skills and knowledge (brain gain). The present study aims to explore the factors influencing the intentions for return migration of sub-Saharan African health workers who emigrated to Austria and Belgium, and gain further insight into the potential of circular migration. Methods Semi-structured interviews with 27 sub-Saharan African health workers in Belgium and Austria were conducted. Results As mentioned by the respondents, the main barriers for returning were family, structural crises in the source country, and insecurity. These barriers overrule the perceived drivers, which were nearly all pull factors and emotion driven. Despite the fact that only a minority plans to return permanently, many wish to return regularly to work in the healthcare sector or to contribute to the development of their source country. Conclusion As long as safety and structural stability cannot be guaranteed in source countries, the number of return migrants is likely to remain low. National governments and regional organizations could play a role in facilitating the engagement of migrant health workers in the development of the healthcare system in source countries.